Determinants of personal bankruptcy, discharge and the role of Islamic social capital: Malaysia and Singapore case - Mohd Isa, Ahmad Mahir (2022)
Individuals adjudged bankrupts are financially incapacitated and restrained by the legal system to employment, entrepreneurship opportunities and formal banking credit facilities. A major concern is the increasing number of personal bankruptcy and undischarged bankrupts, mainly due to high household debts. However, past studies mostly focus on a legal approach to tackle this issue. Hence, the main objective of this study is to examine the influence of macroeconomic variables on bankruptcy and discharge in Malaysia and Singapore, which represent developed and developing economies. Gross Domestic Product (GDP), Consumer Price Index (CPI), Interest Rate (IR), Household debt (HD) and Unemployment (UE) were tested on bankruptcy (Model B) and discharge (Model D). Another objective is to assess the effect of integrating an Islamic social capital variable called social-relief-fund (SRF) in the discharge model (Model DIs). This fresh approach is based on the concept of Al-nahd and Ta’awun. The analysis used ARDL and Variance Decomposition on annual time series data over a 20- year (2000-2019) period covering long-run and short-run relationships. The significant factors for Bankruptcy for long-run are IR and HD; CPI and HD for Malaysia and Singapore, respectively. For DIs, SRF is only significant in Malaysia. For short run, CPI is highly significant for Model B, Model D and Model DIs. SRF is highly significant in increasing discharge in the long run. However, it shows a positive effect for Malaysia and negative influence for Singapore. The findings of this study provide new empirical contributions to bankruptcy and discharge literature. Important research implications are two- folds; i) Policy implication, that is, Islamic social finance can be a good social safety net to the financially distressed Muslim and non-Muslim individuals and ii) Practical implication where the debt repayment scheme should be inflation rate-adjusted to account for changes in the macroeconomic environment